The trajectory of intrahelical lesion recognition and extrusion by the human 8-oxoguanine DNA glycosylase - Uddhav K. Shigdel (Nature Portfolio, 2020)
DNA glycosylases are lesion-specific enzymes that recognize specific nucleobase damages and catalyze their excision through cleavage of the glycosidic bond. Here, the authors present the crystal structures of human 8-oxoguanine (oxoG) DNA glycosylase bound to undamaged DNA and to DNA containing an intrahelical oxoG lesion and further analyse these structures with molecular dynamics simulations, which allows them to characterise the base-extrusion pathways.